2003
DOI: 10.1148/rg.236025174
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Imaging of Paratesticular Neoplasms and Their Rare Mimics

Abstract: Extratesticular neoplasms are rare but clinically significant lesions that affect patients of all ages. These neoplasms are generally asymptomatic but may have potentially life-threatening sequelae. Lipoma is the most common primary benign paratesticular neoplasm and the most common tumor of the spermatic cord. Adenomatoid tumor is the most common tumor of the epididymis, followed by leiomyoma. In adult patients, it is imperative to consider sarcomas in the differential diagnosis of all solid tumors of the scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
274
0
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(291 citation statements)
references
References 21 publications
4
274
0
13
Order By: Relevance
“…However, a confident preoperative characterization of various benign intratesticular entities, including dilatation of rete testis, orchitis, epidermoid cyst, infarction, fibrosis and hematoma, for which radical orchiectomy is unnecessary is important. [3][4][5][6][7][8] In these patients, a more conservative approach, as follow-up, tumor enucleation or testissparing surgery may be justified. Sonography, although the primary imaging technique for the evaluation of scrotal pathology, 1,2 because of its wide availability, low cost and high sensitivity in the identification of scrotal lesions, does not always allow a confident preoperative characterization of scrotal masses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a confident preoperative characterization of various benign intratesticular entities, including dilatation of rete testis, orchitis, epidermoid cyst, infarction, fibrosis and hematoma, for which radical orchiectomy is unnecessary is important. [3][4][5][6][7][8] In these patients, a more conservative approach, as follow-up, tumor enucleation or testissparing surgery may be justified. Sonography, although the primary imaging technique for the evaluation of scrotal pathology, 1,2 because of its wide availability, low cost and high sensitivity in the identification of scrotal lesions, does not always allow a confident preoperative characterization of scrotal masses.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] The technique due to its wide field of view, multiplanar capabilities, high contrast and spatial resolution has proved satisfactory in the localization of a scrotal mass, in the differentiation of paratesticular masses with respect to tumor morphology and tissue characteristics, in the distinction between benign from malignant intratesticular lesions and in the evaluation of the local extent of the disease in cases of testicular carcinomas. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The technique is mainly recommended when sonographic findings are inconclusive or inconsistent with clinical findings. 5,6 In accordance with previous reports, this study demonstrated high accuracy of conventional MR sequences in characterizing both paratesticular and intratesticular mass lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Para realizar diagnósticos diferenciales en cuanto a otras patologías que aparecen como masas extratesticulares escrotales, se puede uti- lizar la resonancia nuclear magnética sin haberse determinado características típicas de estos tumores ni generalizarse su uso 6 .…”
Section: Discussionunclassified